2009
DOI: 10.1158/0008-5472.can-09-0786
|View full text |Cite
|
Sign up to set email alerts
|

The CHRNA5-CHRNA3-CHRNB4 Nicotinic Receptor Subunit Gene Cluster Affects Risk for Nicotine Dependence in African-Americans and in European-Americans

Abstract: Genetic association studies have shown the importance of variants in the CHRNA5-CHRNA3-CHRNB4 cholinergic nicotinic receptor subunit gene cluster on chromosome 15q24-25.1 for the risk of nicotine dependence, smoking, and lung cancer in populations of European descent. We have carried out a detailed study of this region using dense genotyping in both European-Americans and African-Americans. We genotyped 75 known single nucleotide polymorphisms (SNPs) and one sequencing-discovered SNP in an African-American sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
228
5
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(260 citation statements)
references
References 33 publications
17
228
5
7
Order By: Relevance
“…15 Previous GWAS and replication studies have found associations between IREB2 polymorphisms and COPD and COPD-related phenotypes. 5,11,14,15 However, because the region of chromosome 15q25 where IREB2 gene is located was found to be linked to nicotine addiction, [18][19][20][21] and there is high levels of LD between SNPs in IREB2 and SNPs in CHRNA3/5 in this region, 5 association findings in IREB2 may be the result of independent association with smoking behavior or the result of high LD with SNPs in the CHRNA3/5 gene cluster, and key functional variants may actually be in the CHRNA3/5 gene cluster. We identified two SNPs in IREB2 associated with COPD in non-smoking subjects, in the same direction as previously reported, while the association was not observed in current-smokers and Analyses of pulmonary function phenotypes were adjusted for age, gender, BMI, current smoking status and pack-years by linear regression; analyses of pack-years for ever-smoker were adjusted for age, gender and current smoking status by linear regression.…”
Section: Association Of Ireb2 and Chrna3/5 With Copd In A Chinese Hanmentioning
confidence: 99%
“…15 Previous GWAS and replication studies have found associations between IREB2 polymorphisms and COPD and COPD-related phenotypes. 5,11,14,15 However, because the region of chromosome 15q25 where IREB2 gene is located was found to be linked to nicotine addiction, [18][19][20][21] and there is high levels of LD between SNPs in IREB2 and SNPs in CHRNA3/5 in this region, 5 association findings in IREB2 may be the result of independent association with smoking behavior or the result of high LD with SNPs in the CHRNA3/5 gene cluster, and key functional variants may actually be in the CHRNA3/5 gene cluster. We identified two SNPs in IREB2 associated with COPD in non-smoking subjects, in the same direction as previously reported, while the association was not observed in current-smokers and Analyses of pulmonary function phenotypes were adjusted for age, gender, BMI, current smoking status and pack-years by linear regression; analyses of pack-years for ever-smoker were adjusted for age, gender and current smoking status by linear regression.…”
Section: Association Of Ireb2 and Chrna3/5 With Copd In A Chinese Hanmentioning
confidence: 99%
“…Human genetic studies have highlighted the polymorphic nature of the CHRNA5-CHRNA3-CHRNB4 genomic cluster, encoding subunits α5, α3, and β4, and its implication in smoking behaviors (Bierut et al, 2008). Furthermore, variants in the β4 regulatory domain reduce the age of tobacco initiation, while gain-offunction variants in CHRNB4 reduce the risk of nicotine dependence (Haller et al, 2012;Saccone et al, 2009;Schlaepfer et al, 2008). Although cholinergic responses are unaffected in CHRNB4 coding variants, nicotine-elicited currents are increased (Haller et al, 2012), which is reflected as aberrant nicotine aversion in mice expressing these variants (Slimak et al, 2014), and as fewer cigarettes smoked per day in humans (Haller et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Most prominent among these are the human genetic association studies showing that single nucleotide polymorphisms in the gene cluster CHRNA5/Α3/Β4, encoding for the α3, α5, and β4 nAChR subunits, are closely associated with the risk for heavy smoking, inability to quit, and increased sensitivity to nicotine. [7][8][9][10][11] Further, studies in knockout mice show that the β4 nAChR subunit is necessary for nicotine withdrawal because withdrawal is greatly diminished in β4 null mice, but not in β2 null mice. 12,13 Unlike the wide distribution of α4β2 nAChR in the brain, the α3 and β4 subunits are expressed in a restricted number of brain areas, mainly the medial habenula and interpeduncular nucleus, major cholinergic tracts in the brain that have recently garnered increasing attention for their involvement in various aspects of nicotine dependence.…”
Section: Introductionmentioning
confidence: 99%